2017
DOI: 10.1186/s12934-017-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose on poly-γ-glutamic acid metabolism in Bacillus licheniformis

Abstract: BackgroundPoly-gamma-glutamic acid (γ-PGA) is a promising macromolecule with potential as a replacement for chemosynthetic polymers. γ-PGA can be produced by many microorganisms, including Bacillus species. Bacillus licheniformis CGMCC2876 secretes γ-PGA when using glycerol and trisodium citrate as its optimal carbon sources and secretes polysaccharides when using glucose as the sole carbon source. To better understand the metabolic mechanism underlying the secretion of polymeric substances, SWATH was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Thus, mutations may occur in the genes encoding the enzymes for the lactose, mannose and galactose metabolism pathways. It was reported that glucose can affect the γ-PGA synthetic enzyme system and catabolite control protein A (CcpA) [34]. CcpA possesses several functions, such as control of lactose transport, β-galactosidase activity, and glycolysis [35], CcpA represses the TCA cycle and activates the EMP pathway when glucose is present in the medium [36].…”
Section: Effect Of Carbon Sources On γ-Pga Production By B Siamensismentioning
confidence: 99%
“…Thus, mutations may occur in the genes encoding the enzymes for the lactose, mannose and galactose metabolism pathways. It was reported that glucose can affect the γ-PGA synthetic enzyme system and catabolite control protein A (CcpA) [34]. CcpA possesses several functions, such as control of lactose transport, β-galactosidase activity, and glycolysis [35], CcpA represses the TCA cycle and activates the EMP pathway when glucose is present in the medium [36].…”
Section: Effect Of Carbon Sources On γ-Pga Production By B Siamensismentioning
confidence: 99%
“…In contrast, in B. licheniformis , the carbon metabolism regulatory proteins CcpA and CcpN and the nitrogen metabolism regulatory protein NrgB played core roles in the transition between the metabolism of the polysaccharide and γ-PGA. CcpA and CcpN could co-enhance glycolysis and suppress the carbon flux in the TCA cycle, consequently slowing the synthesis of γ-PGA; simultaneously, CcpN could cut off the carbon flux from glycerol metabolism and further reduce the γ-PGA production [ 37 ]. The synthesis of γ-PGA was also influenced by NrgB, which could transform the major nitrogen metabolic flux between NH 4 + and glutamate, facilitate ammonium utilization and promote glutamine synthesis; these effects are all beneficial for γ-PGA synthesis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…CcpA and CcpN could co-enhance glycolysis and suppress the carbon flux in the TCA cycle, consequently slowing the synthesis of γ-PGA; simultaneously, CcpN could cut off the carbon flux from glycerol metabolism and further reduce the γ-PGA production [ 37 ]. The synthesis of γ-PGA was also influenced by NrgB, which could transform the major nitrogen metabolic flux between NH 4 + and glutamate, facilitate ammonium utilization and promote glutamine synthesis; these effects are all beneficial for γ-PGA synthesis [ 37 ]. Our results also showed that overexpressing epsB could reduce the expression of CcpA and CcpN while increasing the expression of NrgB, all of which improved the γ-PGA synthesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When a rapid-acting carbon source (glucose) is present in a fermentation system, the utilization priority of the rapid-acting carbon source is higher than that of the inducer, causing the inducer (another sugar or alcohol)-related genes to be inhibited by the CcpA protein and subjecting the expression system to the CCR effect ( Jankovic and Brückner, 2007 ; Moreno et al., 2010 ). When a delayed carbon source is present in a fermentation system, the inducer (sugar or alcohol) is the fast-acting carbon source, and the related metabolic utilization genes involved are activated by the CcpA protein, thereby causing the expression system to be subjected to the CCA effect ( Yu et al., 2017 ). Sugar/alcohol-inducible promoters usually contain a classical CRE site in the core region ( Heravi et al., 2011 ; Ren et al., 2010 ), which makes the regulation of the CcpA protein particularly important for the promoter.…”
Section: Discussionmentioning
confidence: 99%